‘Exceptional’ Open Prisons Under Pressure: Austerity, Instability and Distrust - Nyvoll, Pernille Søderholm (The British journal of criminology, 2025)
This article examines the impact of various challenges on two Norwegian low-security prisons, Bastøy and Leira, during a particularly demanding period. Using ethnographic fieldwork and in-depth interviews with 51 prisoners, the article applies the conceptual metaphors ‘depth’, ‘weight’, and ‘tightness’ to explore the severity of control, restriction and psychological burden. Findings reveal a reduction in activities and an increase in restrictiveness in both prisons. Additionally, prisoners at Bastøy noticed reduced staff presence and deteriorated trust, possibly due to the prison’s larger size, workplace conflicts and complex restructuring process, exacerbated by COVID-19 restrictions and austerity measures. The results point to a diminishing ‘exceptionality’ in Norwegian prisons, highlighting the importance of stability, institutional autonomy, and smaller prison size in fostering trust and close relationships.